A pilot randomized controlled trial of a commercial diet and exercise weight loss program in minority breast cancer survivors1. (16th March 2013) - Greenlee, Heather A.; Crew, Katherine D.; Mata, Jennie M.; McKinley, Paula S.; Rundle, Andrew G.; Zhang, Wenfei; Liao, Yuyan; Tsai, Wei Y.; Hershman, Dawn L.
Abstract: Objective: Obesity is associated with poorer breast cancer outcomes and losing weight postdiagnosis may improve survival. As Hispanic and black women have poorer breast cancer prognosis than non‐Hispanic whites diagnosed at similar age and stage, and have higher rates of obesity, effective weight loss strategies are needed. We piloted a randomized, waitlist‐controlled, crossover study to examine the effects and feasibility of the commercial Curves weight loss program among Hispanic, African American and Afro‐Caribbean breast cancer survivors. Design and Methods: Women with stage 0–IIIa breast cancer ≥6 months posttreatment, sedentary, and BMI ≥25 kg/m 2 were randomized to the immediate arm (IA): 6 months of the Curves program followed by 6 months of observation; or the waitlist control arm (WCA): 6 months of observation followed by 6 months of the Curves program. The Curves program uses a 30‐min exercise circuit and a high‐vegetable/low‐fat/calorie‐restricted diet. Results: A total of 42 women enrolled (79% Hispanic, 21% black), mean age 51 (range 32–69) and mean BMI 33.2(±5.9) kg/m 2 ; 91% were retained at month 12. At month 6, women in the IA lost an average 3.3% (±3.5%) of body weight (range: 1.7% gain to 10.6% loss), as compared with 1.8% (±2.9%) weight loss in the WCA ( P = 0.04). At month 12, on average women in the IA regained some but not all of the weight lost during the first 6 months ( P = 0.02). Conclusions: Minority breast cancer survivors were recruited and retained in a weight loss study. Six months of the Curves program resulted in moderate weight loss, but weight loss was not maintained postintervention. Future interventions should identify methods to increase uptake and maintenance of weight loss behaviors.